Hyperoperation sequence #
This file defines the Hyperoperation sequence.
hyperoperation 0 m k = k + 1
hyperoperation 1 m k = m + k
hyperoperation 2 m k = m * k
hyperoperation 3 m k = m ^ k
hyperoperation (n + 3) m 0 = 1
hyperoperation (n + 1) m (k + 1) = hyperoperation n m (hyperoperation (n + 1) m k)
References #
Tags #
hyperoperation
@[irreducible]
Implementation of the hyperoperation sequence
where hyperoperation n m k
is the n
th hyperoperation between m
and k
.
Equations
- hyperoperation 0 x✝ x = x + 1
- hyperoperation 1 x 0 = x
- hyperoperation 2 x 0 = 0
- hyperoperation n.succ.succ.succ x 0 = 1
- hyperoperation n.succ x k.succ = hyperoperation n x (hyperoperation (n + 1) x k)
Instances For
theorem
hyperoperation_recursion
(n : ℕ)
(m : ℕ)
(k : ℕ)
:
hyperoperation (n + 1) m (k + 1) = hyperoperation n m (hyperoperation (n + 1) m k)
theorem
hyperoperation_ge_four_zero
(n : ℕ)
(k : ℕ)
:
hyperoperation (n + 4) 0 k = if Even k then 1 else 0